Designing world language curriculum for intercultural communicative competence - Eddy, Jennifer (London ; New York : Bloomsbury Academic, 2022)
"This book creatively redefines how teacher educators and faculty in secondary and post-secondary language education can become designers with intercultural education in mind. The author aligns theoretical frameworks with practical features for revising the modern language curriculum via themes and novel tasks that transfer language learning from classroom to community, developing communicative competence for mediation and learner autonomy along the way. For novice and experienced instructors alike, this book empowers them to: - design curriculum from transferable concepts that are worthy of understanding and have value within the culture(s) and to the learner; - develop assessments that ask the learner to solve problems, and create products that transfer concepts or address needs of various audiences that they will encounter in community, life, and work; - direct language learners through a spiral, articulated program that supports academic, career and personal goals."--
Preface -- 1. Unfolding Curriculum With No End in Mind -- 2. (Re)Imagining Curriculum to Reveal the Cultural Story -- 3. From Coverage Without Pity to Designing With Performance for Transfer: Make it New Everyday -- 4. Designing for Interpretive Goals: Exploring Meaning for Mediation -- 5. Designing for the Interpersonal Goal: Consensus on Meaning for Mediation -- 6. Designing for Presentational Goals: Creating Meaning for Mediation -- 7. Putting it Together for Articulation and Transfer -- References -- Index.
Includes bibliographical references and index.
Also issued in print: Bloomsbury Academic, 2022. Digital resource published 2022.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Description based on online resource; title from digital title page (viewed on August 26, 2022).
Keywords: Language and languages -- Study and teaching -- Curricula; Intercultural communication; Language and languages -- Ability testing; Curriculum planning & development; Language teaching & learning material & coursework; Examinations & assessment; Secondary schools; Higher & further education; tertiary education; Electronic books